Polymer viscoelasticity : basics, molecular theories, and experiments - Lin, Y.-H (World Scientific, 2003)
In this book, the studies of the Rouse, Doi-Edwards, and extended reptation theories are developed in a consistent manner from a basic level and discussed in detail. Viscoelastic properties of nearly monodisperse linear flexible polymers in both the entanglement and entanglement-free regions are analyzed quantitatively in terms of the molecular theories.